2020
DOI: 10.3390/antiox9111074
|View full text |Cite
|
Sign up to set email alerts
|

Olive Mill and Winery Wastes as Viable Sources of Bioactive Compounds: A Study on Polyphenols Recovery

Abstract: In this study, the recovery of polyphenols from olive oil mill and winery waste was investigated. The performance of ultrasound assisted extraction (UAE), microwave assisted extraction (MAE), and pressurized liquid extraction (PLE) was assessed using ethanol–water mixtures, which are compatible with food, nutraceutical, and cosmetic applications. The extraction efficiency from olive pomace and lees samples was evaluated in terms of total polyphenol content (TPC), determined by high performance liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 50 publications
(27 reference statements)
3
40
0
Order By: Relevance
“…The UAE treatment was confirmed to be particularly effective for the recovery of hydroxytyrosol, maslinic acid, and oleanolic acid from olive pomace compared to the conventional one [ 32 ]. Tapia-Quirós et al [ 33 ] effectively extracted phenolic compounds from olive pomace by applying UAE for 30 min with 50% ( v / v ) ethanol, proposing this technique as an ideal candidate for future increased evaluation. By combining ultrasounds with enzymes, the extraction efficiency of phenolic compounds from olive pomace can be further improved.…”
Section: Valorization Of Olive Pomacementioning
confidence: 99%
See 1 more Smart Citation
“…The UAE treatment was confirmed to be particularly effective for the recovery of hydroxytyrosol, maslinic acid, and oleanolic acid from olive pomace compared to the conventional one [ 32 ]. Tapia-Quirós et al [ 33 ] effectively extracted phenolic compounds from olive pomace by applying UAE for 30 min with 50% ( v / v ) ethanol, proposing this technique as an ideal candidate for future increased evaluation. By combining ultrasounds with enzymes, the extraction efficiency of phenolic compounds from olive pomace can be further improved.…”
Section: Valorization Of Olive Pomacementioning
confidence: 99%
“…According to the results, the microwave treatment (600 W at 50 °C for 5 min) resulted in extracts with 8%, 24%, and 22% higher concentration of hydroxytyrosol, maslinic acid, and oleanolic acid, respectively, than those obtained by conventional extraction for 240 min. Tapia-Quirós et al [ 33 ] and Jurmanović et al [ 36 ] effectively extracted phenolic compounds from olive pomace by applying MAE at 90 °C for 5 min with 50% ( v / v ) ethanol, and for 10 min with 20% ( v / v ) ethanol, respectively.…”
Section: Valorization Of Olive Pomacementioning
confidence: 99%
“…Other wastes are also produced during the filtration processes and during the storage time when the solid components migrate to the tank bottoms, generating sediments. These waste products are rich in bioactive compounds and can be therefore considered valuable byproducts to be exploited for further uses [ 39 , 40 ]. Although OMWs are effluents capable of degrading soil and water quality, with serious negative effects on the environment [ 7 ], studies have revealed that they contain high concentrations of antioxidants, such as phenolic molecules [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although OMWs are effluents capable of degrading soil and water quality, with serious negative effects on the environment [ 7 ], studies have revealed that they contain high concentrations of antioxidants, such as phenolic molecules [ 41 ]. However, since the quality of OMW compounds differs according to the olive variety, the technological process of olive oil production, storage time, and climatic conditions [ 40 ], it is imperative to evaluate the technological processes employed in OMW processing in order to obtain valuable bioactive compounds. In this regard, phenolic compounds derived from OMW have been reported to show interesting biological properties [ 10 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation